2018
DOI: 10.1007/s10610-018-9372-7
|View full text |Cite
|
Sign up to set email alerts
|

Foreign National Prisoners in Flanders (Belgium): Motivations and Barriers to Participation in Prison Programmes

Abstract: This exploratory study examines the experiences of foreign national prisoners and the motivations and barriers to their participation in prison programmes (e.g., educational courses, use of the prison library, prison work, sociocultural activities, sports). Data are derived from 15 individual interviews with foreign national prisoners in two Belgian prisons. During the interviews the strengths-based approach of Appreciative Inquiry was used. The results demonstrate that foreign national prisoners experience mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 34 publications
(59 reference statements)
0
25
0
Order By: Relevance
“…This study showed that, once foreign nationals have access to prison activities and services, they still experience some participation difficulties. Informal peer support took place to deal with the difficulties foreign nationals experience during participation, such as language barriers and staff shortages (Croux et al, 2019b). In particular, informational and instrumental peer support are provided or received during participation to overcome difficulties that are more pronounced for foreign nationals, such as a lack of information and the language problem.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that, once foreign nationals have access to prison activities and services, they still experience some participation difficulties. Informal peer support took place to deal with the difficulties foreign nationals experience during participation, such as language barriers and staff shortages (Croux et al, 2019b). In particular, informational and instrumental peer support are provided or received during participation to overcome difficulties that are more pronounced for foreign nationals, such as a lack of information and the language problem.…”
Section: Discussionmentioning
confidence: 99%
“…Perceived future benefits in employment and a regular life pull them into rehabilitation programs. In addition to potential economic benefits, inmates participate in prison programs also to acquire perceived social and psychological rewards (Cai et al, 2019; Croux, Brosens, Vandevelde, & De Donder, 2019; Hall & Killacky, 2008; Papaioannou et al, 2018; Schlesinger, 2005; Tewksbury & Stengel, 2006; Torre & Fine, 2005).…”
Section: Prior Researchmentioning
confidence: 99%
“…Regarding psychological benefits, researchers have found that some inmates are attracted into various prison programs with the hope of acquiring higher self-esteem and self-efficacy, greater confidence, and to achieve self-improvement and personal fulfillment (e.g., Croux et al, 2019; Papaioannou et al, 2018; Tewksbury & Stengel, 2006). At the same time, inmates are often motivated by social reasons.…”
Section: Prior Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…This is what the research presented below involves, exploring the ways to respond and the motivation of prison staff. Employees play the role of animators of penitentiary work, teachers, and mentors; therefore, they should have not only specific cultural competences but also personality predispositions (Croux et al 2018), using the quality of their personal relationship with an individual in this work. A resource for this relationship is one's own life experiences and personal history because working with these convicts is above standard (Brosens et al 2020).…”
Section: Introductionmentioning
confidence: 99%